FINANCIAL MANAGEMENT TRAINING FOR FISHERMEN IN INDRAMAYU TO SUPPORT BLUE ECONOMY IMPLEMENTATION - Rabbaniyah, Lathiefah; Riyantie, Mayang; Utari, Eka Dewi; Suhendry, Bayu; Zahra, Siti Fatimah; Pramudya, Alfonsus Liguori; Lestari, Sri (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2025)
This community service initiative aims to enhance financial literacy and family financial management skills among fishing communities in Karangsong Village, Indramayu Regency, to support the implementation of blue economy principles. Low levels of financial literacy have contributed to the inability of fishers to manage their highly fluctuating incomes, increasing household economic vulnerability, particularly during the lean season. This program involves various activities, including socialization sessions, basic financial record-keeping training, budgeting workshops, education on emergency funds, and improving understanding of access to formal financial services. The outcomes of this initiative include improved knowledge and skills among fishers in managing household finances, developing budgeting habits, adopting basic financial record-keeping practices, and initiating a savings culture. In line with the sustainable development goals of the blue economy, this effort is expected to strengthen the economic resilience of fishing families, reduce their dependency on middlemen, and promote smarter financial behavior.